Ubicación óptima de PMUS basado en criterios de observabilidad y evaluación mediante búsqueda tabú - Jaramillo Perugachi, Carlos Andrés (2016)
The steady growth of electricity networks has made it imperative to use new technologies to improve the reliability of the electrical system, Phasor Measurement Units (PMUs) are devices advanced metering suited to provide relevant information, such information improves safety and reliability system, however one of the crucial points is to determine the optimal location for a complete observability of the system, minimizing the total number of PMU's installed, thus achieving minimize the use of server space. In the present work is to determine the optimal location of the PMU's using an meta-heuristic called tabu search, it will be find the best solution to the problem, meeting all the parameters and constraints of the proposed objective function. For the modeling of the problem is taken as examples of test models IEEE 14, 30 and 118 bars, subsequently the analysis of results of each system is performed and compared with other optimization algorithms such as genetic algorithm, modified harmony search and optimization by swarm of binary particles.